Private equity unchained : strategy insights for the institutional investor - Meyer, Thomas; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
There are significant returns to be made from private equity, infrastructure, real estate and other illiquid investments, but a competitive strategy is essential for investment success and for meeting objectives. This book takes readers through all the considerations of planning and implementing an investment strategy in illiquid investments.
Keywords: Private equity; Corporate governance; Portfolio management